Tinjauan Teoritis Likuiditas Dan Profitabilitas Terhadap Nilai Perusahaan - Annisa Fadillah; Shita Tiara; Sri Elviani (Jurnal Ilmiah Akuntansi Kesatuan, 2021)
The value of the company is the selling value of the company or the value of growth for shareholders, the value of the company is reflected in its share price. The main goal of the company is to maximize the value of the company. Increasing the value of the company can also increase investment opportunities by investors so that companies can get additional sources of funds. The purpose of this study is to examine the effect of profitability, liquidity on firm value on the Indonesian stock exchange. The results of this study indicate that (1) liquidity does not affect firm value and (2) profitability affects firm value. Simultaneously, liquidity and profitability affect the value of banking companies listed on the IDX. Keywords : Liquidity, Profitability, Firm Value, IDX